2022
DOI: 10.1021/acs.inorgchem.1c03534
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Packing-Driven Selective Hg(II) Ion Sensing Using Thiazolothiazole-Based Water-Stable Zinc Metal–Organic Framework

Abstract: A soft acid-soft base interaction is highly predictable. However, we demonstrate how the crystal packing of the newly synthesized zinc framework [Zn 2 (5-AIA) 2 (DPTTZ)]•DMF (where 5-AIA = 5-aminoisophthalic acid, DPTTZ = N,N′-di(4-pyridyl)thiazolo- [5,4-d]thiazole, DMF = N,N′-dimethylformamide) directs an unexpected interaction between the soft acid Hg(II) and the hard base oxygen instead of having a soft center like nitrogen and sulfur in the system attributed to a strong solvent interaction and a favorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 54 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…S16b †). 55 All these results clearly indicated the hydrolytic robustness of PABA@MOF-808 which is advantageous for the practical implementation of the probe for the aqueous phase NO sensing study.…”
Section: Resultsmentioning
confidence: 77%
“…S16b †). 55 All these results clearly indicated the hydrolytic robustness of PABA@MOF-808 which is advantageous for the practical implementation of the probe for the aqueous phase NO sensing study.…”
Section: Resultsmentioning
confidence: 77%
“…When the Eu-ttpd solution was irradiated with a 650 nm laser beam, the Faraday-Tyndall effect could be observed both initially and after 30 min without sparking in the path of the laser beam, thus demonstrating the homogeneous dispersion of the Eu-ttpd solution (Figure S12). In addition, dynamic light scattering showed that the average diameter of the particles in this homogeneously dispersed solution was 21 μm (Figure S13). To demonstrate the expected detection performance of Eu-ttpd on PGA, a series of selectivity experiments were carried out for different substances in urine systems including glucose (Glu), hippuric acid, creatinine, DL-mandelic acid, urea, Na + , K + , Mg 2+ , NH 4 + , and PGA.…”
Section: Resultsmentioning
confidence: 98%
“…The bond lengths of Zn-O (1.932-2.060 Å) and Zn-N (1.932-2.060 Å) both are in the normal ranges, respectively. [55][56][57][58][59][60] The two L1 3− ligands in each asymmetric unit both adopt the μ 3 -η 0 : η 1 : η 1 : η 0 : η 1 : η 0 coordination mode (mode III, Scheme S1 †). The Zn1 ions are connected to L1 3− anions by O1 and O5 to form zigzag one-dimensional chains (Fig.…”
Section: Resultsmentioning
confidence: 99%